1995
DOI: 10.1111/j.1600-0447.1995.tb09781.x
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone versus zuclopenthixol in the treatment of acute schizophrenic episodes: a double‐blind parallel‐group trial

Abstract: A double-blind, randomized, multi-center, parallel-group study was conducted in Finland to compare the efficacy and safety of risperidone with zuclopenthixol in patients with acute exacerbations of schizophrenia or schizophreniform disorder. Ninety-eight patients were randomly assigned to treatment with risperidone (n = 48) or zuclopenthixol (n = 50), in variable doses, for 6 weeks. The mean daily doses of risperidone and zuclopenthixol at the end of the trial were 8 mg and 38 mg respectively. Efficacy was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 23 publications
(19 reference statements)
4
37
0
3
Order By: Relevance
“…It also possesses some short-acting norepinephrine receptor antagonist activity, as well as some antihistaminergic activity (Leysen et al 1988;Janssen et al 1988). Studies have shown that it is at least as effective as the typical neuroleptics in patients with acute and chronic schizophrenia with positive and/or negative symptoms (Chouinard et al 1993;Hoyberg et al 1993;Marder and Meibach 1994;Carman et al 1995;Huttunen et al 1995;Peuskens and the Risperidone Study Group 1995) and that it is better tolerated than typical neuroleptics in terms of extrapyramidal side effects (Geddes et al 2000).…”
mentioning
confidence: 99%
“…It also possesses some short-acting norepinephrine receptor antagonist activity, as well as some antihistaminergic activity (Leysen et al 1988;Janssen et al 1988). Studies have shown that it is at least as effective as the typical neuroleptics in patients with acute and chronic schizophrenia with positive and/or negative symptoms (Chouinard et al 1993;Hoyberg et al 1993;Marder and Meibach 1994;Carman et al 1995;Huttunen et al 1995;Peuskens and the Risperidone Study Group 1995) and that it is better tolerated than typical neuroleptics in terms of extrapyramidal side effects (Geddes et al 2000).…”
mentioning
confidence: 99%
“…However, the differences between the 2 drugs in schizophrenia subjects have been pointed out elsewhere (6,13). In samples with and without dual diagnosis, risperidone and zuclopenthixol were equally effective in reducing positive, but not negative, symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Zuclopenthixol is a well-established thioxanthene antipsychotic. Zuclopenthixol's controlled studies have shown that this antipsychotic is as effective as chlorpromazine (12) and risperidone (13) in the treatment of schizophrenia patients. It can be administered intramuscularly or orally.…”
mentioning
confidence: 99%
“…In the original review, 23 studies were identified for inclusion: Blin 1996, 251 Borison 1991, 252 Bouchard 1998, 253 Ceskova 1993, 254 Chouinard 1993, 255 Claus 1991, 256 Emsley 1995, 257 Hoyberg 1993, 258 Huttunen 1995, 259 Mahmoud 1998, 260 Marder 1994, 116 Mesotten 1991, 261 Min 1993, 262 Peuskens 1995, 263 Fleurot 1997, 62 Bondolfi 1998, 110 Anand 1998, 111 Breier 1999, 112 Wahlbeck 2000, 113 Tran 1997, 171 Klieser 1996, 264 Jones 1998, 193 Gureje 1998. 186 Data extraction sheets for these studies are presented in appendix 3.…”
Section: Old Rctsmentioning
confidence: 99%